Mastering Dreamweaver 4 and Fireworks 4 - Crowder, David A.; Chowder, Rhonda (San Francisco Sybex Inc., 2001)
Includes hand coding and the layout view found in Dreamweaver, along with the pop-up menu creator found in Fireworks. Includes practical advice on developing your site's architecture, and enhancing interactivity into your site's design.
Keywords: Dreamweaver (Computer file); Fireworks (Computer file); Web sites -- Authoring programs